Sipintar: A MOOC-Based Platform to Improve Reading Learning Outcomes - Vendra Ardiansyah; Syukri Hamzah; Agus Trianto (Script Journal: Journal of Linguistics and English Teaching, 2025)
Background: This study is motivated by the pressing challenge of improving reading skills among elementary school students in rural areas, particularly in Penukal Utara, where access to quality educational resources is limited. The aim of this research is to assess the effectiveness of the "Sipintar" MOOC-based platform in enhancing students' reading abilities, addressing a critical need in these underserved regions. Methodology: The study employed a quasi-experimental design, specifically a one-group pretest-posttest format. The sample comprised 72 fourth-grade students from four different elementary schools. Reading ability data was collected through standardized reading tests conducted both before and after the intervention, and the results were analyzed using paired t-tests to determine the significance of any improvements. Findings: The results demonstrated a significant enhancement in students' reading abilities following their use of the Sipintar platform. The majority of students exhibited marked progress, providing strong evidence of the platform’s efficacy in boosting reading performance among elementary students in rural settings.. Conclusion: The Sipintar platform has proven to be an effective tool for improving reading skills among elementary school students in Penukal Utara. Given its success, the platform holds promise for broader implementation in other remote regions facing similar challenges in access to quality educational materials. Originality: This study fills a critical gap by offering empirical evidence on the effectiveness of a MOOC-based platform for enhancing reading skills in rural areas, where educational resources are frequently inadequate.